Respuesta :
Focus of the parabola is (2,-1) and directrix is y = -1/2.
Let's assume a point (x,y) on parabola.
According to definition of parabola, the distance between point (x,y) and focus (2,-1) would be same as the distance between the point (x,y) and directrix y = -1/2.
[tex]\sqrt{(x-2)^2+(y+1)^2} = \sqrt{(y+\frac{1}{2}) ^2} \\\\(x-2)^2+(y+1)^2=(y+\frac{1}{2} )^2 \\\\(x-2)^2 + y^2 + 2y +1 = y^2 +y +\frac{1}{4} \\\\(x-2)^2 = -y^2 - 2y -1 + y^2 +y +\frac{1}{4} \\\\(x-2)^2 = -y -1 +\frac{1}{4} \\\\(x-2)^2 = -y +\frac{-4+1}{4} \\\\(x-2)^2 = -y +\frac{-3}{4} \\\\y = -(x-2)^2 +\frac{-3}{4} \\\\[/tex]
Hence, option D is correct, i.e. f(x) = −(x − 2)² − three fourths.
Answer:
[tex]y = - (x - 2)^2 - \frac{3}{4}[/tex]
Step-by-step explanation:
The parabola must have all the points to be equally distant from the point of focus and the directrix, where directrix a horizontal line and the focus being a point given.
To derive an equation for the parabola, we will use the formula of distance. Now we have a random point on the parabola (x,y) and the point (x,y) will be equidistant from the focus and the directrix. So using the distance formula, we will get:
[tex]\sqrt{(y -(\frac{-1}{2}}))^2} = \sqrt{(x-2)^2 + (y - (-1)^2}[/tex]
The square root of y-(-1/2) from the directrix, and the righthand side of the equal sign is derived from the focus point. Now simplify it to get:
[tex](y + \frac{1}{2} )^2 = (x - 2)^2 + (y + 1)^2[/tex]
[tex]y^2 + y + \frac{1}{4} = x^2 - 4x +4 + y^2 + 2y + 1[/tex]
[tex]-y - \frac{3}{4} = x^2 - 4x + 4[/tex]
[tex]-y = (x - 2)^2 + \frac{3}{4}[/tex]
[tex]y = - (x - 2)^2 - \frac{3}{4}[/tex]
.